2020
DOI: 10.1088/1757-899x/791/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

The study of ecological impact of fly ash-based geopolymer binders on soil and aquatic biota

Abstract: Coal power plants represent the large source of environmental pollution in soils, ground and surface water by leaching out toxic compounds from open landfilled and impounded coal combustion residuals (CCR) such as fly ash. The use of fly ash as a main component in geopolymer binder (GB) systems is one of the effective methods of CCR beneficial utilization. The toxicity assessment as well as leachability of harden geopolymers were tested in aqueous media where oat seeds were used as affected test objects. Bio-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…and FA67K 1,000. Differently from published results on FA-based AAMs, focused on fungicidal properties of some FA products ( Vasilenko et al, 2020 ), we investigated the effect on bacteria, either gram-positive ( E. faecalis ) or gram-negative ( E. coli ). Experimentally, we demonstrated that there is no obvious negative effect on bacterial growth, thus declaring a safe coexistence of the developed geopolymers with the ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…and FA67K 1,000. Differently from published results on FA-based AAMs, focused on fungicidal properties of some FA products ( Vasilenko et al, 2020 ), we investigated the effect on bacteria, either gram-positive ( E. faecalis ) or gram-negative ( E. coli ). Experimentally, we demonstrated that there is no obvious negative effect on bacterial growth, thus declaring a safe coexistence of the developed geopolymers with the ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Geopolymer concrete (GPC) has the advantages of environmental protection and energy savings, as well as mechanical properties close to or better than OPC concrete (OPCC) [ 16 , 17 , 18 , 19 , 20 ]. Besides, GPC will show higher temperature resistance on some structures, compared to OPCC [ 21 ].…”
Section: Introductionmentioning
confidence: 99%